Pour une promotion de la santé lesbienne : état des lieux des recherches, enjeux et propositions - Clotilde Genon; Cécile Chartrain; Coraline Delebarre (Genre, Sexualité et Société)
The authors analyse and synthesize a range of international studies on « lesbian health ». Though they may be based on different populations and sampling methods which are sometimes problematic, these surveys describe the impact of discriminations and negative representations on lesbians, because of their gender as well as of their sexual orientation. The following questions are addressed in detail: mental health, use of psychoactive products, cancers and cardio-vascular pathologies, sexual health, domestic violence between lesbian partners. These topics were selected for their potential to assess precisely the health inequalities encountered by these women. Beyond the literature review, this article is concluded with recommendations, which aim at facilitating the emergence of an environment that empowers lesbians and gives them control over their own health.